Lignin accumulation in cell wall plays a role in clubroot resistance - Tu, Jiangying; Qin, Li; Karunakaran, Chithra; Wei, Yangdou; Peng, Gary (Frontiers in Plant Science, 2024)
Clubroot, caused by Plasmodiophora brassicae, is a significant disease affecting brassica crops worldwide and poses a threat to canola (Brassica napus) production in western Canada. Management of this disease heavily relies on the use of resistant cultivars, but resistance erosion is a serious concern due to the highly diverse pathogen populations. Understanding resistance mechanisms may aid in better deployment/rotation of clubroot resistance (CR) genes and improve resistance resilience. In this study, we conducted a comparative analysis using resistant canola varieties carrying either a single (Rcr1) or double CR genes (Rcr1+Crr1 rutb ) to decipher the resistance modes associated with these genes. Neither resistant variety affected the primary infection of root hairs/epidermal cells compared to the susceptible "Westar", but both exhibited strong inhibition of cortical infection, effectively 'trapping' the pathogen in the exodermis. Cell wall (CW) biopolymeric compounds in different root cell layers were mapped and quantified using Fouriertransform mid-infrared microspectroscopy; the most prominent change observed was increased lignin accumulation associated with resistance. In Westar, the pathogen was able to degrade CW lignin, facilitating access to the root cortex by secondary plasmodia of P. brassicae. In contrast, resistant varieties showed clear lignin accumulation around the penetration site on the exodermis, accompanied by elevated expression of genes involved in the phenylpropanoid pathway. These results suggest that induced lignin accumulation plays a role in clubroot resistance mediated by the CR genes Rcr1 and Crr1 rutb in canola, providing cellular and structural evidence that supports the data from earlier transcriptomic studies.